Coral dos desafinados: uma escuta para a inclusão musical - Maria Beatriz Maciel Myrrha (2024)
The present research has, as the subject of study, the Coral dos Desafinados, a group composed of adults without prior musical training and/or who felt excluded for being considered “out of tune” in some context of their lives. Given the significant number of complaints from individuals who do not feel musical or who do not sing because they feel out of tune (Sobreira, 2002), contrasted with the few publications and offers of musical education and inclusion courses for this profile (Santos, 2023), the study aims at understanding the significance of the choir Coral dos Desafinados in the lives of its participants, analyzing whether the processes and practices developed in its context constitute possible musical inclusion, concerning the restoration of confidence in singing and on the musical making. In the formation of the theoretical framework, the research conducted a literature review on musical inclusion (Penna, 2018; Swanwick, 2003), vocal out-of-tuneness (Carvalho, 2019; Fernandes, 2021; Sobreira, 2017), and narrative (Bosi, 1994; Benjamin, 2012; Estés, 2014; Machado, 2004). In the context of qualitative research, data collection instruments included a questionnaire administered to participants to survey the group's profile and their relationship with music and the Choir. An interview was also conducted with one of the participants using the narrative interview technique (Bauer and Jovchelovitch, 2012; Muylaert et al., 2014; Pachá and Moreira, 2022; Petrucci-Rosa et al., 2017) to capture information with a greater degree of depth and subjectivity. In light of the theoretical foundation, the data were analyzed and categorized through the production of Benjaminian monads (Petrucci-Rosa et al., 2017). The results identified the feasibility of musical inclusion promoted by the Coral dos Desafinados, as indicators of musical, emotional, and social benefits were detected, as well as improvements in the participants' self-identification regarding their musicality and ability to sing.